THE PAINTER BOGOS TATIKIAN OF SMYRNA AND THE ALBUM OF LITHOGRAPHY PREPARED AS A GIFT TO THE NATIONAL LIBRARY OF THE UNITED STATES - Semra DAŞÇI (Fırat University, 2019)
This study deals with a painter and lithographer Bogos Tatikian (1820 - ?) of Smyrna who was an Ottoman Armenian and was considerably active in Smyrna in 19th century. In addition, using some new documents this study aims to evaluate the Tatikian Printing House served for a long time in Smyrna and Tatikian’s contributions to the cultural and artistic environment of the city. In the commercial annuals published on various dates in Izmir during the 19th century and the early 20th century, the name of the Tatikian Printing House is commonly observed. The latest publications of the Tatikian Printing House are dated from 1922 and after then its name is unable to find in documents and trade annuals. The lithographer and painter Bogos Tatikian began to paint in 1840s. The street scenes reflected the local characteristics in order to attract the attention of foreign tourists were mostly painted by the artist. These large size images commonly contained a single figure and represented the street vendors and the costumes of the different nations of the city. In addition, Tatikian prepared and printed to sell the colored and gilded portraits of the Ottoman Sultans. His engraving albums are appeared in various museums and private collections in domestic and abroad. One of these albums is held at Istanbul Metropolitan Municipality, Ataturk Library. This album was commissioned by the Sultan Abdulhamid II. for the National Library of United States of America. It contains 29 colored engravings depicted the vendors and the peoples from different religions and nationalities like Armenians, Turks, Jews, Albanians in Smyrna. Although we were unable to reach all details of his life, the works left by him reveals that he was an eager and lively artist.